The trend of surface ozone in Beijing from 2013 to 2019: Indications of the persisting strong atmospheric oxidation capacity - SY Chen; Wang, H. C.; Lu, K. D.; L.M. Zeng; Hu, M.; Zhang, Y. H. (Atmospheric Environment, 2020)
We report a continuous record of surface ozone (O-3) in urban Beijing, China, from 2013 to 2019. A linear fit to the 7-year record shows that the annual MDA8-O-3 (the maximum daily average of 8-h O-3 concentration) and annual average O-3 increased by 2.30 and 1.91 ppbv yr(-1) (p < 0.05), respectively. Both the MDA8-O-3 level and the number of exceeding days are increased, demonstrating the surface O-3 pollution in Beijing is increasingly serious. An overall decrease in annual surface NO2 was observed at a rate of -1.21 ppbv yr(-1) (p < 0.01). The total oxidants (O-x, = NO2 + O-3) had an upward trend during 2013-2019 at a rate of 0.70 ppbv h(-1) (p = 0.168). The increasing O-3 and Or trends imply the atmospheric oxidation capacity is increasing in Beijing, even though the strict emission policies have been implemented. The periodical changes of surface O-3 in different time scales are studied. We found that the increases in O-3 are mainly at a high O-3 level with a threshold of 30 ppbv. The relative diurnal variability of surface O-3 is weakened, with a decrease in the diurnal amplitude variation. Both the extremely low and high 5% surface O-3 are increased, indicates an overall uplift of surface O-3. The weekday periodic trends showed an increment of weekend MDA8-O-3 (2.2 ppbv on average) and companies with a decrement of weekend NO2 (1.5 ppbv on average). The weekend effect provides a chance to look insights into reducing O-3 exceeding days during summertime and proposes the need for emission abatements of volatile organic compounds to the mitigation of ozone pollution in Beijing.
Keywords: air-quality; beijing china; China; emissions; long-term trend; nitrogen-oxides; ozone pollution; photochemistry; pollution; precursors; rural site; the trend of o-3; urban; weekend; weekend effect